The Effect of Pressure Ulcers on the Survival in Patients With Advanced Dementia and Comorbidities. Issue 4 (7th August 2016) - Jaul, Efraim; Meiron, Oded; Menczel, Jacob
Abstract : Background/Study Context : The mortality rates for many leading causes of death have declined over the past decade. Advanced dementia with comorbidities has steadily increased to become one of the leading causes of death in the elderly population. Therefore, this study examined the effect of pressure ulcers on the survival time of patients with advanced dementia and comorbidities. Methods : Data were reviewed from all the files of 147 patients hospitalized over a period of 3½ years. Ninety-nine tube-fed patients suffering from advanced dementia were assessed; 72 (66.5%) had pressure ulcers and 27 (33.5%) were without pressure ulcers at admission. Logistic regression analysis was used to estimate the odds ratio and 95% confidence intervals for pressure ulcers group versus non–pressure ulcers group. Unadjusted Cox model and Cox proportional hazards model were used to assess the hazard ratio for pressure ulcers and the association between pressure ulcers and survival time, respectively. Kaplan-Meier model was used to visually confirm the existence of proportional hazards of pressure ulcers on survival. Results : The median survival of advanced dementia patients with pressure ulcers was significantly shorter, compared with those without pressure ulcers (96 vs. 863 days). Significant lower hemoglobin and serum albumin levels were found in the patients with pressure ulcers. Conclusion : Advance dementia and pressure ulcers in the same patient results in earlier mortality. Advanced dementia patients with pressure ulcers had significantly lower survival expectancy in comparison with similar patients without pressure ulcers. Clinical and ethical implications are discussed.